Preparation of a miR-155-activating nucleic acid nanoflower to study the molecular mechanism of miR-155 in inflammation - Wenxin Wang; Jie Geng; Xiaohan Wu; Jianguang Zhang; Chenna Zheng; Huachun Rao; Tianyu Li; Yong Diao; Huiyong Yang (BMC, 2022)
Abstract At present, the molecular mechanisms underlying inflammation remain unclear. In recent years, research on inflammation has focused on stimulating cell inflammation by using exogenous pro-inflammatory substances such as lipopolysaccharide (LPS) or inflammatory factors. To investigate the molecular mechanism of inflammation from a new perspective, we designed a nucleic acid nanoflowers (NFs) complex to directly activate inflammatory genes to study the inflammatory response without the need for external microbial factors to trigger an inflammatory response. An RNAa-type target gene-activated NFs was designed. Human umbilical vein endothelial cells (HUVECs) were transfected with NFs carrying small activating RNA (saRNAs) to directly co-activate microRNA (miR)-155 and SHIP1 genes. After RNA activation (RNAa)-type NFs were transferred into HUVECs, the expression of miR-155 and pro-inflammatory and cancer-related factors increased, anti-inflammatory factors were reduced, cell proliferation increased, and cell migration was promoted. IL-1β protein levels were decreased and SHIP1 expression was downregulated. When miR-155 and its target SHIP1 were both activated, the expression of both was unaltered, maintaining cell homeostasis. This points towards miR-155 overexpression can trigger inflammation, and that miR-155 and its target genes act as a molecular switch role in the development of inflammation.